The subtype-specific role of histone H1.0 in cancer cell differentiation and intratumor heterogeneity - Roque, Alicia; Ponte, Inma; Suau, Pedro (Translational Cancer Research; Vol 6, Supplement 2 (March 31, 2017): Translational Cancer Research, 2017)
Cancer originates in a single cell. However, most human tumors present extensive intratumor heterogeneity and comprise several populations with distinct phenotypes. Intratumor heterogeneity have to be considered in the design of treatment strategies. Torres et al. (1) has identified an epigenetic mechanism that creates intratumor functional heterogeneity. They report that reversible silencing of histone H1 subtype H1.0 affects the differentiation state of cancer cells.